Gulag 113 - Kolga, Marcus (Realworld Pictures, 2005)
Verzio FF submission Duration: 00:47:00 An 89 year old Estonian-Canadian returns to his former home to retrace a terrifying journey to hell that began in 1941. Traveling from Estonia to the northern Russian town of Kotlas where his Gulag labor camp was located, the film follow Eduard as he remembers how he escaped death and reconciles with dark memories. It’s a classic story of one man overcoming insurmountable hardships. The documentary also features rare historical footage and beautifully captured images from locations in Canada, Estonia and Russia.